Mitochondrial regulatory mechanisms in spinal cord injury: A narrative review. Issue 46 (18th November 2022) - Liu, Chengjiang; Liu, Yidong; Ma, Boyuan; Zhou, Mengmeng; Zhao, Xinyan; Fu, Xuanhao; Kan, Shunli; Hu, Wei; Zhu, Rusen
Abstract : Spinal cord injury is a severe central nervous system injury that results in the permanent loss of motor, sensory, and autonomic functions below the level of injury with limited recovery. The pathological process of spinal cord injury includes primary and secondary injuries, characterized by a progressive cascade. Secondary injury impairs the ability of the mitochondria to maintain homeostasis and leads to calcium overload, excitotoxicity, and oxidative stress, further exacerbating the injury. The defective mitochondrial function observed in these pathologies accelerates neuronal cell death and inhibits regeneration. Treatment of spinal cord injury by preserving mitochondrial biological function is a promising, although still underexplored, therapeutic strategy. This review aimed to explore mitochondrial-based therapeutic advances after spinal cord injury. Specifically, it briefly describes the characteristics of spinal cord injury. It then broadly discusses the drugs used to protect the mitochondria (e.g., cyclosporine A, acetyl-L-carnitine, and alpha-tocopherol), phenomena associated with mitochondrial damage processes (e.g., mitophagy, ferroptosis, and cuproptosis), mitochondrial transplantation for nerve cell regeneration, and innovative mitochondrial combined protection therapy.